Pengaruh Produk Dan Kualitas Layanan Terhadap Loyalitas Konsumen Starbucks Coffe Di Samarinda - Sarwo Edi Wibowo, Gusti Kiyak Pahlawan LCA Robin Jonathan (EKONOMIA, 2020)
The Purpose of this study aims to know How is the Quality of Product And Quality of Service Influence to the Loyalty Starbucks Coffee Samarinda Consumers.This Study was done at Samarinda city. The sample used in this study were 97 respondents with a Non Probability Sampling Method and the technique sampling is Purposive Sampling. Data was collected by distributing questionnaires and using likert scale for each indicator. The Analytical tool used is Multiple Linear Regression at SPSS V23 Programm.The result of this study show : the Quality of Product Variable was significantly influence to the Loyalty Starbucks Coffee Samarinda Consumers, the Quality of Service Variable was significantly influence to the Loyalty Starbucks Coffee Samarinda Consumers, and the Quality of Product and Quality of Service was simultaneously significant influence to the Loyalty Starbucks Coffee Samarinda Consumers